A computationally efficient framework for the simulation of the nonlinear seismic performance of infilled RC frame buildings. (15th May 2022) - Bose, Supratik; Stavridis, Andreas
Highlights: This study proposes a computationally efficient box modeling framework to simulate the seismic response of infilled RC frames. The box model has four columns at the corners connected by beams and diagonal struts along the perimeter that represents an actual building. The framework combines the backbone curves of the individual bays of the building to estimate the overall lateral resistance of the structure in two main orthogonal directions. This simplified framework can successfully capture the overall response and damage pattern of test specimens and actual buildings. Abstract: This study proposes a novel approach for the computationally efficient numerical modeling of the nonlinear seismic response of entire buildings with infilled RC frames. The proposed modeling framework can be particularly helpful for buildings with multiple stories and complex layouts, for which the current methods can be cumbersome to implement, or inaccurate. This framework combines the force-vs.-displacement response for every bay of the building to obtain the envelop curves for every floor along the two main perpendicular horizontal directions. These curves are used to calibrate a box-type model of the building. The proposed methodology is employed to simulate the response of a two-bay, three-story frame tested on a shake table, and an instrumented four-story school building in Nepal, damaged by the 2015 Gorkha earthquake. The comparison of the numerical results with the test and field data indicates that the proposed approach can accurately capture the important features of the seismic response of the actual structures and their dynamic properties.